Metamorfosis Kurban dalam Agama Islam dan Yahudi - Rambe, Mahlaini; Harahap, Elly Warnisyah; Paralihan, Hotmatua (ANWARUL, 2023)
The Metamorphosis of Sacrifice in Islam and Judaism. This change will be seen from the point of view of the implementation of the sacrifice from the time of the Prophet Adam, the prophet Abraham to the time of the prophet Muhammad as the bearer of the last treatise. This study of the metamorphosis of sacrifice is the background of this research problem. The author will look at related issues, namely: how is the metamorphosis of sacrificial worship in Islam and Judaism. This discussion also examines the similarities and differences in sacrifice in Islam and Judaism. In this way, it will be known how sacrifices are made in Islam and Judaism so that there will be differences between the two. This type of research approach used by the author is Library Research. The data analysis uses the comparative (comparative) method of Islam and Judaism, with a theological approach. The result of this research is that the sacrifice is prescribed, it is introduced to humans in the form of offerings to God according to what they have. In the period between Prophet Adam and Prophet Abraham, the sacrificial service was changed to a ritual offering of offerings to idols, which were worshiped by the prophets of Noah, the prophets of Hud and the people of the prophet Salih. At the time of the prophet Abraham, the transformation of the sacrifice was changed to an offering by slaughtering a good lamb. The transformation of sacrificial worship after the time of the prophet Abraham was by leading the fire as a sign of acceptance of the sacrifice. Furthermore, during the time of the Prophet Muhammad, the sacrificial service was carried out by slaughtering sacrificial animals in the form of Bahimah Al An'am (livestock), which was carried out after carrying out the Eid al-Adha prayer. Whereas in Judaism, the first Sacrifice order was carried out by Abraham to Isaac's son but was replaced with a lamb. The command to sacrifice changed from human to animal.